Pengaruh Kesadaran Wajib Pajak, Pemahaman Pajak, Tarif Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak - Kellyn; Handra Tipa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The compliance level of SME taxpayers significantly impacts a country's economy. However, there are still a number of SME taxpayers who have not fulfilled their obligations. Discrepancies occur between the expected number of SME taxpayers to report and the actual number of SME taxpayers reporting. This research employs a quantitative approach to examine the influence of taxpayer awareness, tax understanding, tax rates, and tax sanctions on the compliance of SME taxpayers in KPP Pratama Batam Selatan. A sample of 100 respondents was selected using purposive sampling method. Data collection involved the distribution of questionnaires, and the data analysis utilized multiple linear regression analysis processed with SPSS 25. The results of this study indicate that, individually, taxpayer awareness and tax understanding have a significant effect on taxpayer compliance, while tax rates and tax sanctions do not affect taxpayer compliance. Simultaneously, taxpayer awareness, tax understanding, tax rates, and tax sanctions significantly influence the compliance of SME taxpayers